Project-Based Learning to Enhance Students’ Creative Thinking Skill on Language Learning - ARIFATIN, FAIS WAHIDATUL (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2023)
This research investigates the effectiveness of project-based learning in enhancing students' creative thinking skills in language learning. The aim is to explore the impact of project-based learning strategies, collaboration, technology integration, and real-world contexts on students' creative thinking abilities. Qualitative research approach was utilized, including surveys, observations, and project assessments. This research was applied to students at MTS Muhammadiyah 13 Solokuro who are currently starting to use the independent curriculum (Kurikulum Merdeka) in grade 7. The results indicate a positive impact of project-based learning on students' creative thinking skills, with improvements observed in idea generation, critical thinking, and problem-solving abilities. Collaboration and communication were found to be crucial elements in fostering creative thinking. The integration of technology and real-world contexts further enhanced students' creativity. The study highlights the importance of project-based learning in promoting students' motivation and engagement in language learning. However, there is a need for further research to explore long-term effects, individual differences, assessment strategies, teacher professional development, comparative studies, and generalizability. These findings provide insights for educators to effectively implement project-based learning and cultivate students' creative thinking skills in language education.